Sosialisasi Peran Literasi Perpustakaan dalam Bentuk Library Tour bagi Siswa Sekolah Menengah Atas di Pekalongan - Prayogi, Arditya; Asirah, Khusnu; Thohirin, Thohirin; Septiani, Nora (Kifah: Jurnal Pengabdian Masyarakat, 2024)
College libraries have the task of being a system that supports the implementation of the tridharma of higher education, which in this case is community service activities. Broadly speaking, libraries have a role in collecting, processing, storing, presenting and disseminating information to the public. In this case, it means that libraries have a role in building a literate generation. For this reason, there needs to be an activity that can improve abilities in the field of library information literacy. It was against this background that this service activity was carried out. This activity was carried out using the socialization method and a library tour with activity participants who came from high school students in Pekalongan with the aim of improving library information literacy skills. From the results of the activity, it was found that this activity ran well and smoothly and had impacts/benefits that could be felt directly by the activity participants.